Pentahelix-Based Msme Development Strategy To Reduce The Unemployment Rate In Tebing Tinggi City - Bunga Anggraini; Muhammad Syahbudi; Nursantri Yanti (Universitas Trunodjoyo Madura, 2025)
This study aims to formulate a development strategy for Micro, Small, and Medium Enterprises (MSMEs) based on the Pentahelix approach to reduce unemployment in Tebing Tinggi City. The Pentahelix approach involves five main elements: academics, businesses, communities, government, and mentors, who collaborate in the local economic development process. The methodology is a qualitative one, including statistical data, questionnaires, in-depth interviews, document analysis, and observation as data collecting methods. The strategy is analyzed using the SOAR (Strengths, Opportunities, Aspirations, Results) framework and the Triple Bottom Line (TBL) principle, which includes social (people), environmental (planet), and economic (profit) aspects. The analysis results show that the combination strategy of Opportunities + Aspirations (OA) is the most optimal approach, with the highest score in the IFAS and EFAS analyses. The OA strategy is considered capable of utilizing external opportunities such as technological innovation, strategic partnerships, community collaboration, and policy support, to realize the aspirations of sustainable community economic empowerment. These findings demonstrate the importance of cross-sector collaboration in encouraging MSME growth as a strategic solution to reduce unemployment in the region.Keywords: MSMEs, Pentahelix, Unemployment, SOAR